PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSETS, RETURN ON EQUITY DAN NET PROFIT MARGIN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SUBSEKTOR KONSTRUKSI BANGUNAN YANG TERDAFTAR DI BEI - Juwari Juwari; Arrum Mustika Zulviani (Jurnal GeoEkonomi, 2020)
This research aims to determine the effect of simultaneously and partially variables of Debt to Equity Ratio, Return on Assets, Return on Equity and Net Profit Margin on profit growth. The research period used is 2015-2018. The population in this study are companies that are incorporated in the building construction subsector which are listed on the Indonesia Stock Exchange as many as 19 companies. This research uses Purposive Sampling technique so that 11 company samples are obtained, using secondary data in the form of annual financial statement data of the building construction subsector for the 2015-2018 period. The data analysis technique used in this study is multiple linear regression analysis with the help of SPSS version 25. The results of this study indicate that simultaneously Debt to Equity Ratio, Return on Assets, Return on Equity and Net Profit Margin have a positive and significant effect on profit growth in building construction subsector companies listed on the Indonesia Stock Exchange. While partially it can be concluded that of the four variables the Net Profit Margin has a dominant effect on profit growth in the building construction subsector company listed on the Indonesia Stock Exchange.